2017
DOI: 10.1007/s00228-017-2230-6
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam population pharmacokinetics in children with epilepsy aged 1 month to 16 years

Abstract: PurposeThe aims of the study were to develop a population pharmacokinetic model of orally administered brivaracetam in paediatric patients and to provide dosing suggestions.MethodsAnalysis included 600 brivaracetam plasma concentrations from a phase 2a study (NCT00422422; N01263) in 96 paediatric patients with epilepsy aged 1 month to 16 years, taking one to three concomitant antiepileptic drugs (AEDs). Pharmacokinetic analysis was performed using non-linear mixed effects modelling, and a stepwise covariate se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…PK parameters in healthy participants are not significantly affected by age. 69 In participants aged >75 years, t ½ is slightly longer and clearance slightly lower compared with those aged 65–75 years; however, these changes are not considered significant enough to require a dose adjustment in elderly patients. 70…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
See 2 more Smart Citations
“…PK parameters in healthy participants are not significantly affected by age. 69 In participants aged >75 years, t ½ is slightly longer and clearance slightly lower compared with those aged 65–75 years; however, these changes are not considered significant enough to require a dose adjustment in elderly patients. 70…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…72 In pediatric epilepsy patients, population PK analysis found that BRV exposure was reduced by 29% and 32% with concomitant administration of phenobarbital and carbamazepine, respectively, and increased by 11% with valproate. 69 …”
Section: Pharmacokinetic Profilementioning
confidence: 99%
See 1 more Smart Citation
“…A reason for these differences might be the methodology of the studies. The previous studies either used population PK modeling in adults 4 or children, 15 or investigated PK in healthy subjects 14 . In PK modeling, the effect of covariates on AED plasma clearance is estimated, which can be translated into other parameters, such as the change in average daily concentration.…”
Section: Discussionmentioning
confidence: 99%
“…В дальнейшем часть пациентов перешла в долгосрочное наблюдение, часть -закончила исследование с постепенным снижением дозы. Исследование N0 126 673 -долгосрочное исследование бриварацетама III фазы у пациентов в возрасте ≤17 лет -в настоящее время продолжается, и ожидается публикация о безопасности и переносимости бриварацетама у детей [17].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified